Successful living donor liver transplantation for classical maple syrup urine disease. (20th June 2016) - Yasui, Toshihiro; Suzuki, Tatsuya; Hara, Fujio; Watanabe, Shunsuke; Uga, Naoko; Naoe, Atsuki; Yoshikawa, Tetsushi; Ito, Tetsuya; Nakajima, Yoko; Miura, Hiroki; Sugioka, Atsushi; Kato, Yutaro; et al.
Abstract: MSUD is an autosomal recessive condition characterized by a deficiency in the enzyme, BCKDH, which catalyzes the breakdown of BCAAs. If left untreated, MSUD can result in mental retardation, central nervous system disorders, and even death. Most patients with MSUD are treated with a restricted protein diet and milk from which BCAAs have been removed. LT has been shown effective in patients with MSUD. This report describes the case of a 15‐month‐old boy who received a liver graft from his mother. Transplantation was successful, and the patient was then able to ingest a normal diet. Despite episodes of acute rejection, chylous ascites, and high fever (40 °C), he has shown no evidence of MSUD recurrence. These findings indicate that patients with MSUD can be successfully treated by LDLT, even when the donor is a heterozygous carrier of a mutated BCKDH gene.